2021
DOI: 10.3389/fnbeh.2021.649129
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Intersection of Nicotine, Gene Expression, and Behavior

Abstract: The cholinergic system plays a crucial role in nervous system function with important effects on developmental processes, cognition, attention, motivation, reward, learning, and memory. Nicotine, the reinforcing component of tobacco and e-cigarettes, directly acts on the cholinergic system by targeting nicotinic acetylcholine receptors (nAChRs) in the brain. Activation of nAChRs leads to a multitude of immediate and long-lasting effects in specific cellular populations, thereby affecting the addictive properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 221 publications
(307 reference statements)
0
8
0
Order By: Relevance
“…The transcriptional profile associated with immune activation is significantly different in adolescent microglia as compared to adult microglia ( 148 ). Nicotine treatment showed age-dependent effects on microglial marker Iba1 expression in the NAc and BLA which are actively maturing brain region during adolescence responsible for reward ( 66 ).…”
Section: Methodsmentioning
confidence: 99%
“…The transcriptional profile associated with immune activation is significantly different in adolescent microglia as compared to adult microglia ( 148 ). Nicotine treatment showed age-dependent effects on microglial marker Iba1 expression in the NAc and BLA which are actively maturing brain region during adolescence responsible for reward ( 66 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, experiencing the pleasurable effects of nicotine and avoiding withdrawal symptoms that contribute to maintained use and relapse behavior (4). Long-term nicotine use leads to gene expression alterations that promote the development of the trajectory of nicotine dependence (6). Chronic nicotine exposure also induces epigenetic modifications, including DNA methylation of several genes in different areas of the brain, such as in the medial prefrontal cortex (mPFC), dorsolateral prefrontal cortex (dLPFC), orbitofrontal cortex (OFC), and nucleus accumbens (NAc) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking induces DNA methylation and changes in gene expression in the brain and widespread alterations in pulmonary, cardiovascular, hepatic, and adipose tissue (12). Several studies have demonstrated that DNA methylation can be used as a predictor in human behavior for nicotine dependence, withdrawal, or relapse (6). Numerous factors affect epigenetic modifications in human smokers, including the duration of nicotine exposure, brain region, sex, and diet (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cholinergic system controls a variety of complex cognitive processes, such as attention, sensorimotor gating, cognitive flexibility, reinforcement, learning, and memory ( Court et al, 1999 ; Miwa et al, 2006 , 2011 ; Tekinay et al, 2009 ; Zhang et al, 2010 ; de la Salle et al, 2013 ; Freitas et al, 2013 ; Chen et al, 2018 , 2020 ; Solari and Hangya, 2018 ; Anderson et al, 2020 ; Sherafat et al, 2021 ). Integral to the cholinergic system are the nicotinic acetylcholine receptors (nAChRs).…”
Section: Introductionmentioning
confidence: 99%